A meshfree analysis of the thermal behaviors of hot surface glass pane subjects to down-flowing water film via smoothed particle hydrodynamics. (November 2020) - Abdoh, D.A.; Ademiloye, A.S.; Liew, K.M.
Abstract: Glass cooling using water film depends on several parameters such as heat flux, down-flowing velocity, and thickness of water film. The efficiency of glass protection with water film can be significantly enhanced through a proper combination of the fire and water film parameters. This study aims to present an in-depth investigation into the influence of the heat flux, down-flowing velocity and thickness of water film parameters on the thermal behavior of glass panes during a fire and to propose new guidelines to enhance the efficiency of the water film glass protection system. Smoothed particle hydrodynamics (SPH) method is used here to simulate glass cooling with a down-flowing water film. Based on several SPH simulation scenarios of glass cooling at a different fire and water film working conditions, new empirical equations are derived to describe the effects of heat flux, down-flowing velocity, and thickness of water film on the temperature drop in glass and water film. Furthermore, these empirical equations were employed to study the evaporation of water film and to compare the efficiency of the cooling mechanism with different down-flowing velocity and thickness of water film. The simulation results confirm that increasing down-flowing velocity is more efficient in glass cooling than increasing water film thickness.